2013
DOI: 10.1158/1078-0432.ccr-11-2701
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Involvement of Immune Pathways in the Therapeutic Response and Outcome in Breast Cancer

Abstract: The immune system could mediate the antitumor activity of several anticancer treatments. Several chemotherapy compounds, including anthracyclines and oxaliplatin, induce immunogenic cell death that in turn activates antitumor immune response. Trastuzumab induces antibody-dependant cell-mediated cytotoxicity. On the basis of this background, immune markers have recently been the focus of intense translational research to predict and monitor the efficacy of treatments. Gene expression arrays and immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 32 publications
8
146
1
4
Order By: Relevance
“…Finally, at 18 h, the release of HMGB1 from dying tumor cells can be observed. 30,31 In contrast to the results for doxorubicin, our data showed that the levels of HSP70 and HMGB1 peaked at 30 h after exposure to OXA and 5-Fu and gradually decreased afterward. Thus, we evaluated the anti-tumor effect of adjuvant immunotherapy induced by a DC vaccine, including protocols for maturing DCs pulsed with 30-h supernatants.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, at 18 h, the release of HMGB1 from dying tumor cells can be observed. 30,31 In contrast to the results for doxorubicin, our data showed that the levels of HSP70 and HMGB1 peaked at 30 h after exposure to OXA and 5-Fu and gradually decreased afterward. Thus, we evaluated the anti-tumor effect of adjuvant immunotherapy induced by a DC vaccine, including protocols for maturing DCs pulsed with 30-h supernatants.…”
Section: Discussioncontrasting
confidence: 99%
“…Trastuzumab, a mAb, dramatically improves the response rate and progression-free and overall survival of patients with metastatic disease (15). However, the exact mode of action of trastuzumab remains partly elucidated, and several studies have suggested that the inhibition of oncogenic signaling may not be the main mode of action (21,22), in particular when trastuzumab is administered alone for chemotherapy-naïve patients (25,28).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed that the behavior and mechanism of action of trastuzumab may be drastically altered in vitro and in vivo (19,21), and that the relative involvement of signaling inhibition vs. ADCC could be an important determinant of the activity of trastuzumab (25).…”
Section: Trastuzumab As a Preoperative Monotherapy Does Not Inhibit Hmentioning
confidence: 99%
“…In the right context, different subclasses of lymphocytes may exhibit entirely different phenotypes with pro-or anti-tumor roles. 30,34,39 It is thus of paramount importance to discriminate them. One of the first studies to apply rigorous spatial statistics on data from fully automated image analysis investigated clustering patterns of B cells and T cells in healthy and tumor-draining lymph nodes in breast cancer patients.…”
Section: Immune Cellsmentioning
confidence: 99%